A novel prostaglandin I2 agonist, ONO-1301, attenuates liver inflammation and suppresses fibrosis in non-alcoholic steatohepatitis model mice - Satoko Motegi; Atsunori Tsuchiya; Takahiro Iwasawa; Takeki Sato; Masaru Kumagai; Kazuki Natsui; Shunsuke Nojiri; Masahiro Ogawa; Suguru Takeuchi; Yosiki Sakai; Shigeru Miyagawa; Yoshiki Sawa; et al. (BMC, 2022)
Abstract Background ONO-1301 is a novel long-lasting prostaglandin (PG) I2 mimetic with inhibitory activity on thromboxane (TX) A2 synthase. This drug can also induce endogenous prostaglandin (PG)I2 and PGE2 levels. Furthermore, ONO-1301 acts as a cytokine inducer and can initiate tissue repair in a variety of diseases, such as pulmonary hypertension, pulmonary fibrosis, cardiac infarction, and obstructive nephropathy. In this study, our aim was to evaluate the effect of ONO-1301 on liver inflammation and fibrosis in a mouse model of non-alcoholic steatohepatitis (NASH). Methods The therapeutic effects of ONO-1301 against liver damage, fibrosis, and occurrence of liver tumors were evaluated using melanocortin 4 receptor-deficient (Mc4r-KO) NASH model mice. The effects of ONO-1301 against macrophages, hepatic stellate cells, and endothelial cells were also evaluated in vitro. Results ONO-1301 ameliorated liver damage and fibrosis progression, was effective regardless of NASH status, and suppressed the occurrence of liver tumors in Mc4r-KO NASH model mice. In the in vitro study, ONO-1301 suppressed LPS-induced inflammatory responses in cultured macrophages, suppressed hepatic stellate cell (HSC) activation, upregulated vascular endothelial growth factor (VEGF) expression in HSCs, and upregulated hepatocyte growth factor (HGF) and VEGF expression in endothelial cells. Conclusions The results of our study highlight the potential of ONO-1301 to reverse the progression and prevent the occurrence of liver tumors in NASH using in vivo and in vitro models. ONO-1301 is a multidirectional drug that can play a key role in various pathways and can be further analyzed for use as a new drug candidate against NASH.